2021
DOI: 10.18844/cjes.v16i4.6030
|View full text |Cite
|
Sign up to set email alerts
|

Application of multicultural-based learning model syntax of social studies learning

Abstract: This study analyses the differences in knowledge, attitudes and multicultural skills of primary school students divided into two learning models, namely a multicultural-based learning model and a student team achievement division (STAD). This study used a quasi-experiment with two control classes and two experimental classes which were determined through random sampling. Prior to being randomised, an equivalence test was carried out to ensure all classes were equal. The experiment used was a post-test-only con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…This is in accordance with the results of research conducted by Hermino and Arifin (2020), namely if a teacher wants to build an honest character in their students, then that honest character must be accustomed to appearing in the teacher. Furthermore, this is also in accordance with the research of Halonen et al (2020)and Suastika et al (2021)that each indicator of character education is indicated by strategies and learning methods that reflect the value of each character. The learning method in question can be in the form of assignments, learning practices, and habituation so that character education values can be implemented.…”
Section: Discussionsupporting
confidence: 85%
“…This is in accordance with the results of research conducted by Hermino and Arifin (2020), namely if a teacher wants to build an honest character in their students, then that honest character must be accustomed to appearing in the teacher. Furthermore, this is also in accordance with the research of Halonen et al (2020)and Suastika et al (2021)that each indicator of character education is indicated by strategies and learning methods that reflect the value of each character. The learning method in question can be in the form of assignments, learning practices, and habituation so that character education values can be implemented.…”
Section: Discussionsupporting
confidence: 85%
“…Slavin (1980, as cited in Kim, 2018) at that time defined the model as operational instructional approach in which learners are rewarded for score they obtained as a team. STAD is a highly structured (Ishtiaq, Ali, & Salem, 2017) cooperative instructional model (Kim, 2018) that involves formation of heterogeneous teams (Awada, Burston, & Ghannage, 2020) of four to five members (Suastika et al, 2021) with the ultimate aim of maximizing academic achievement, (Syafril, Rahayu, Wati, & Yuberti, 2018). Zubaidah and Corebima (2021) argued that, STAD is practical model of cooperative instructional approach that accentuates classroom interactions that furnish students with the opportunity to work as a group, motivate, and assist every group member in apprehending a given learning materials for the ultimate purpose of achieving academic excellence hence requires the need of the teacher to monitor group proceedings to ensure active participation of everybody (Nair & Sanai, 2018).…”
Section: Student Teams Achievement Divisions (Stad) Model Of Cooperat...mentioning
confidence: 99%
“…Tri Pramana, meaning three ways to gain knowledge, consists of three parts, including: Pratyaksa-Pramana, Anumana-Pramana and Agama-Pramana [4]. Pratyaksa-Pramana means gaining knowledge by seeing directly, Anumana-Pramana means gaining knowledge by concluding analysis; and Agama-Pramana means gaining knowledge by trusting the notifications of holy people who never lie [5].…”
Section: Design Of Formative-summative Evaluation Model Based Onmentioning
confidence: 99%